2020
DOI: 10.18502/ijph.v49i1.3054
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Modulates Cell Migration and Expression of βCatenin and Epithelial Mesenchymal Transition Markers in Breast Cancer Cells

Abstract: Background: We aimed to assess the effect of sulforaphane (SFN) on breast cancer cell migration and also its effect on the expression of epithelial mesenchymal transition (EMT) markers and β-catenin. Methods: This study was performed in Shahroud University of Medical Sciences, Shahroud, Iran from 2017- 2018. In this experimental study, MDA-MB-231 cells were treated with different concentrations of SFN (5, 10, 20, 30 and 40 μM) at different time points of 24, 48, and 72 h. The control group was untreated cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…EMT is a key step in tumor cell migration and invasion in various types of human cancer ( 39 41 ). Upregulation of N-cadherin induces EMT ( 40 ); another regulator of EMT is E-cadherin, which inhibits the occurrence of EMT and serves as a tumor suppressor ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT is a key step in tumor cell migration and invasion in various types of human cancer ( 39 41 ). Upregulation of N-cadherin induces EMT ( 40 ); another regulator of EMT is E-cadherin, which inhibits the occurrence of EMT and serves as a tumor suppressor ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that pinosylvin decreased MMP-2 protein expression levels and activity, via regulated the activation of zymogen at the post-transcriptional level. EMT is a key step in tumor cell migration and invasion in various types of human cancer (39)(40)(41). Upregulation of N-cadherin induces EMT (40); another regulator of EMT is E-cadherin, which inhibits the occurrence of EMT and serves as a tumor suppressor (41).…”
Section: Discussionmentioning
confidence: 99%
“…Sulforaphane treatment led to the inhibition of cell proliferation of breast cancer cells lines, MCF-7 and MDA-MB-231 and provoked cytotoxic activity by changing cysteine residues of the promyelocytic leukemia protein, known to promote proliferation of the MCF-7 breast cancer cell line ( Alhazmi et al, 2020 ). Sulforaphane has also been shown to modify cell migration and expression of epithelial mesenchymal transition markers that play a large role in breast cancer metastasis ( Bagheri et al, 2020 ).…”
Section: Glucosinolates From Cruciferous Vegetables and Human Healthmentioning
confidence: 99%
“…Aiming to assess the effects of SFN in MDA-MB-231 cells, Bagheri et al. ( 52 ) reported that SFN inhibited cells migration starting at the lower concentration of 5 μM, while induced cell apoptosis only at relatively high doses (30 and 40 µM). Additionally, cells treated with SFN exhibited reduced expression of the EMT markers Fibronectin (starting at 20 µM) and ZEB1 (40 µM), and decreased protein accumulation of β-catenin in a time-dependent fashion upon 40 µM SFN treatment ( 52 ).…”
Section: Cancer Stem Cells and Sulforaphanementioning
confidence: 99%